2020
DOI: 10.1177/1747954120923198
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key career indicators in Portuguese football players

Abstract: The aim of this study was to describe and identify the weight of some key career indicators (KCI) on the competitive level of retirement (professional vs. non-professional) of Portuguese football players. Three thousand five hundred retired Portuguese football players born between 1950 and 1989, and registered on Portuguese Football Federation were considered in this study. Descriptive analysis and a multivariable binary logistic regression model were performed to assess the relationship between the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 33 publications
2
13
1
Order By: Relevance
“…Furthermore, career planning seems to be influenced by the level of self-efficacy of players through the definition of career goals and building plans, helping to trigger the confidence of players in career self-management and decision-making. In fact, as previously pointed out by Monteiro et al (2020) , more than only the definition of goals, the achievement of goals demonstrated strong relation with the age of career retirement and also the level of retirement. However, the most important issue is not to achieve a high level of performance but to maintain such level over the career.…”
Section: Discussionsupporting
confidence: 68%
“…Furthermore, career planning seems to be influenced by the level of self-efficacy of players through the definition of career goals and building plans, helping to trigger the confidence of players in career self-management and decision-making. In fact, as previously pointed out by Monteiro et al (2020) , more than only the definition of goals, the achievement of goals demonstrated strong relation with the age of career retirement and also the level of retirement. However, the most important issue is not to achieve a high level of performance but to maintain such level over the career.…”
Section: Discussionsupporting
confidence: 68%
“…The purpose of this study was to explore the subjective perceptions of the resources and barriers that the employee-athletes have to face in their DC process. It followed the HACM (Wylleman et al, 2013 ), considered one of the most useful models in this type of research (Stambulova and Wylleman, 2019 ; Monteiro et al, 2020 ) as well as the sport career transition model (Stambulova, 2003 ). The results suggest that the employee-athletes perceive interesting resources like the facility for the combination within the private labor sector or an underlying sports identity and, on the other hand, barriers like obstacles in positions within companies not related to sport or the athletes' perceptions about the stakeholders and the aid received in relation to this issue, when it comes to confronting their DC process, constituting a broad range of phenomenological experiences.…”
Section: Discussionmentioning
confidence: 99%
“…In any event, this finding is in line with what in B-WISER ( 2018 ) has been perceived as a resource called self-regulation, which includes planning, self-evaluation, effort, and the self-efficacy. In this regard, it seems that both managers and athletes need to know how to look at the trends of career development during the mastery stage to prepare the retirement transition and their career out of sport (Monteiro et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations